Anthropometrical, physiological and motor tests of high level taekwondo athletes in pre-season phase - Haleva, Y. (The 3rd Wingate Congress of Exercise and Sport Sciences, 2014)
The execution of an elite athlete can be improved by appropriate long-term training. The training condition should be tightly related to the performances of the athlete during competition. The aim of the study was to assess physical tests for high level taekwondo athletes in the preseason period and to compare them with an international level, in order to plan a relevant training (macro-, meso- and micro-cycle) to improve physical abilities. Ten national taekwondo athletes* were tested in different weight categories. Moreover, the ability of the athlete was assessed. For that purpose, the following measures were taken: a 5-m sprint, running back and forth 5 m X 2, isokinetic strength, leg flexibility in sagittal and frontal dimensions, reaction visual time for the legs, squat jump, counter movement jump, drop jump and anaerobic threshold tests, all of which have been shown to be sensitive and to give valid measures of performance in many sports. The physical fitness training comprised aerobic, anaerobic and specific flexibility, coordination, speed, strength and endurance training. Each type of component has a number of subcategories, which allows for a precise execution of the training when the target of the training is predetermined. A very important critical factor when training top athletes is when to do what, i.e. to plan the training.